2016
DOI: 10.1002/ab.21692
|View full text |Cite
|
Sign up to set email alerts
|

Relation between social information processing and intimate partner violence in dating couples

Abstract: We used couple-level data to predict physical acts of intimate partner violence (IPV) from self-reported negative emotions and social information-processing (SIP) abilities among 100 dating couples (n = 200; mean age = 21.45 years). Participants read a series of hypothetical conflict situation vignettes and responded to questionnaires to assess negative emotions and various facets of SIP including attributions for partner behavior, generation of response alternatives, and response selection. We conducted a ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…According to SIP theories (Crick & Dodge, 1994; Holtzworth-Munroe, 1992; Setchell et al, 2017), youth who experience mistreatment in their interpersonal interactions come to see their social world through a biased lens. Thus, rather than the operant learning process emphasized in Akers’ social learning theory (see Akers, 1998; Akers & Jensen, 2006), SIP suggests a learning process whereby individuals develop cognitive models that inform their behavior through repeated interactions with others (Crick & Dodge, 1994; R.…”
Section: The Role Of Anger and Hostile Attribution Bias In Linking Ramentioning
confidence: 99%
See 1 more Smart Citation
“…According to SIP theories (Crick & Dodge, 1994; Holtzworth-Munroe, 1992; Setchell et al, 2017), youth who experience mistreatment in their interpersonal interactions come to see their social world through a biased lens. Thus, rather than the operant learning process emphasized in Akers’ social learning theory (see Akers, 1998; Akers & Jensen, 2006), SIP suggests a learning process whereby individuals develop cognitive models that inform their behavior through repeated interactions with others (Crick & Dodge, 1994; R.…”
Section: The Role Of Anger and Hostile Attribution Bias In Linking Ramentioning
confidence: 99%
“…Within criminology, strain and learning theories have been the dominant explanations for the connection between racial discrimination and violence (Giordano, Copp, Longmore, & Manning, 2016; Setchell, Fritz, & Glasgow, 2017). However, existing research tends to be cross-sectional, does not specify mediators that might account for such a relationship, and does not explore what factors might moderate the association.…”
mentioning
confidence: 99%
“…However, this relational quality became recognizable to them when they perceived it in the child's relation to others, for example the child's mother, where it could be criticized. This also reflects socialinformation theories of interpersonal violence (Murphy 2013), and research demonstrating that men who use IPV have limitations in social information processing (Setchell et al 2017). Hollway (2006) has suggested that the capacity to care develops within early dyadic and triadic family relationships.…”
Section: Discussionmentioning
confidence: 62%
“…From a psychological perspective, human aggression has been linked to poor affect regulation and inadequate socialinformation processing (Crick and Dodge 1996;George et al 2000). In line with this, men's use of intimate partner violence has been associated with aggressive biases in socialinformation processing (Setchell et al 2017). Social information processing that heightens the risk for interpersonal violence has, amongst others, been associated with early trauma and stress during critical neurodevelopmental periods (Golding and Fitzgerald 2019;Murphy 2013).…”
mentioning
confidence: 96%
“…Although there currently no known pharmacological explanations for an association between prescription opioid misuse and IPV, prescription opioid misuse, in particular, may be indicative of a cluster of problem behaviors including IPV or other illicit drug use (Boyd et al, 2009;Fergus & Zimmerman, 2005;Jessor, 1991). Alternatively, individuals may use prescription opioids as a method of coping with the aftermath of IPV (Setchell et al, 2017;Wong et al, 2013). Since 2004, more studies on opioid use and IPV perpetration have been conducted, however, most of the studies either do not distinguish between heroin and prescription opioids (e.g.…”
Section: Drug Use and Ipv Perpetrationmentioning
confidence: 99%